Complejidad, gestión y disipación en la ciudad. Aproximación desde la entropía (2018)
The survival of cities depends, among many other things, on their ecosystem relationship with the surrounding areas, on the efficiency and effectiveness of internal transformation processes, and the local, regional and global supply networks. For this reason, the identification and understanding of material and energy urban demands, the pressure of their discharges, and the level of entropy generated, are needs to act in a timely manner on the relationship functions that can undermine development and deteriorate the own or surrounding environment; at a time when climate vari-ability and global warming reduce the chances of human systems survival. For this reason, it is imperative not only to improve the urban homeostasis and adaptability in emerging economies and to define new models of urban development, but also to manage entropy and promote cyclical flows of materials and energy with low impact on supply and provision systems, and surroundings areas. This initiative proposes a circular urban metabolism, the relocation of generated disorder, its potential conversion into useful information, and obedience of the natural laws and principles by decision makers, as well as citizenship in general.